The rhetorical questions in the poetry of Ángel Rupérez: "Una razón para vivir" - Albaladejo, Tomás (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper deals with the presence and function of rhetorical questions in Ángel Rupérez’s Una razón para vivir (1998). The combination of several kinds of rhetorical questions is studied as to the role of questions in the poematic construction and in its communicative connection with the recipient. The rhetorical configuration of an interrogative axis in the poem is viewed as one of the devices for establishing a special interpretative relationship of the recipient with the whole text of the poem, with the poet and with the poietic process accomplished by the poet. The rhetoricalness of poetry is stressed because of the poetic role of questions and of the interrogative axis.